Partisipasi Masyarakat dalam Pengelolaan Anggaran Pendapatan dan Belanja (APB) - Ainil Wahyudi; Bob Alfiandi; Azwar Azwar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT This study aims to explain, describe and analyze community participation in the management of APB Nagari Padang Sibusuk. The method used in this research is descriptive qualitative research method. Data collection techniques using interview studies, observation and documents. This study was analyzed using the social participation theory of Abdul Aziz Shaleh. The results of the study stated that in the management of the APB Nagari Padang Sibusuk, the community participated in planning, implementation as well as reporting and accountability. The conclusion of the study shows that community participation in the management of APB Nagari Padang Sibusuk as the best Nagari in the Developing Village Index (IDM) 2020, is only procedural participation, and not substantive participation. Keywords: APB Nagari, Community Participation, Forms of Community Participation, Management of APB Nagari.